(3ef QhGFY GdbQBf (B:s (3JCedGJ YdejI hCOHjI aj cJGH Gddg (B/s - (3GdHhWj, eMeO SYjO QeVGfs 1929-2013 ((3OeTb (B- (3ShQjG (B:s (3OGQ GdacQ,s (3HjQhJ (B- (3dHfGf (B:s (3OGQ GdacQ GdeYGUQ,s, 2019)
(3cJGH gh CbQH Gdi JCedGJ YdejI hCOHjI SQjYI aj cJGH Gddg JYGdi, jhVM GdeDda ef hQGFg HYV eG jfWhj Ydjg GdbQBf GdcQje ef QhYI GdHjGf hEYLGRg, heOi JCKjQg aj eNJda GdYdhe GdJj JRNQ HgG GdecJHI GdYQHjI Gdjhe, eeG dGHO ddCOjH hOGQS GdYQHjI ef Gdhbha YfOg(B. (3aaj cJGH Gddg LGfHG COHjG CUjdG HYjO GdLPhQ aj JGQjN GdCOH GdYQHj, YXje GdCKQ aj JhLjgg hJWhjQg hJbhjeg, aef CLd Pdc cGf dGHO def CQGO GdYcha Ydi OQGSI GdYQHjI hBOGHgG ef Cf jYca Ydi OQGSI GdbQBf hYdheg(B.s
Keywords: (3GdbQBfs -- (3JaGSjQ ehVhYjIs; (3GdbQBf s -- (3eHGMK YGeIs